Psychological Interventions for Early Life Trauma in the Digital Age Childhood - Rostami, Mehdi; Arif, Amna (KMAN Counseling & Psychology Nexus, 2023)
The article explores the implications of early life trauma on children's development and the potential of digital technologies to support therapeutic interventions. It begins by outlining the significance of addressing early life trauma, noting the psychological, cognitive, and social challenges that affected children face. The review then delves into current digital interventions, highlighting the benefits and limitations of internet-delivered therapies, mobile apps, and virtual reality in treating and supporting young trauma survivors. It emphasizes the importance of evidence-based, accessible, and engaging digital solutions tailored to the specific needs of children. The discussion extends to ethical considerations, data privacy, and the necessity for professional training in digital tools. Recommendations include developing inclusive digital interventions, fostering interdisciplinary collaboration, and ensuring long-term support for children. The article concludes with a call for continued research, policy development, and the integration of digital innovations into trauma care, advocating for a holistic approach that encompasses the physical, emotional, and social well-being of children in the digital age.